2016
DOI: 10.1111/jors.12302
|View full text |Cite
|
Sign up to set email alerts
|

Destruction and Reallocation of Skills Following Large Company Closures

Abstract: This paper analyzes what happens to redundant skills and workers when large companies close down and whether their skills are destroyed or reallocated. The analysis is based on a combination of qualitative and quantitative data of the closure of four companies. Getting a job in a skill‐related industry or moving to a spinoff firm leads to skill reallocation. Thus, the result depends on regional idiosyncrasies such as industry structure and urbanization. If local policy makers and the owners exert a coordinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…i ϕ denotes individual fixed effects. 9 t ψ represents year-8 This literature shows that a period of involuntary unemployment yields substantial income losses for displaced workers due to a loss of firm-specific knowledge (Couch & Placzek, 2010;Schmieder et al, 2010) and occupational mismatch (Holm, Østergaard, & Olesen, 2016;Nedelkoska, Neffke, & Wiederhold, 2015). In addition, effects on health (Sullivan & von Wachter, 2009), fertility decision (Huttunen & Kellokumpu, 2016), divorce probabilities (Eliason, 2012) and the intergenerational transmission of these effects (Oreopoulos, Page, & Stevens, 2008) have been examined.…”
Section: Identification Approachmentioning
confidence: 99%
“…i ϕ denotes individual fixed effects. 9 t ψ represents year-8 This literature shows that a period of involuntary unemployment yields substantial income losses for displaced workers due to a loss of firm-specific knowledge (Couch & Placzek, 2010;Schmieder et al, 2010) and occupational mismatch (Holm, Østergaard, & Olesen, 2016;Nedelkoska, Neffke, & Wiederhold, 2015). In addition, effects on health (Sullivan & von Wachter, 2009), fertility decision (Huttunen & Kellokumpu, 2016), divorce probabilities (Eliason, 2012) and the intergenerational transmission of these effects (Oreopoulos, Page, & Stevens, 2008) have been examined.…”
Section: Identification Approachmentioning
confidence: 99%
“…People, even within the same country, differ across areas in their interests and identities, that in turn evolve over time as the result of the interaction between historical legacies and the contingent socioeconomic and institutional context: as convincingly argued by Shin and Agnew (2007, p. 300), “[p]olitical change is seldom uniform across a democracy.” Furthermore, places are highly differentiated in terms of their exposure to three main global phenomena shaping the local economy: the higher flows of migrants coming from countries of the Global South, the fiercer trade competition from new international players, and the diffusion of skill‐biased and labor‐substituting technological change. As the transitional costs of adjusting to the shocks associated with globalization and technological progress are significant at the local, sectoral, and individual level (Holm, Ostergaard, & Olesen, 2017), dynamic areas offering opportunities and good jobs coexist with areas of discontent and “places that don't matter” (Rodríguez‐Pose, 2018), where populist, nationalist, and highly conservative narratives gain traction. The empirical approach focusing on the distribution of local voting patterns fits Italy very well, due to the presence of a political environment characterized by changing political parties with nonoverlapping manifestos and considerable regional differentiation in terms of economic structure and electoral results.…”
Section: Introductionmentioning
confidence: 99%
“…Fallick 1996) provides an individual perspective on how human capital is re-used (or not) in new combinations, and it has repeatedly been found that most workers affected by closedowns or major layoffs find new employment shortly after leaving the dispatching firm. Taking this to a regional level, an evolving literature merging economic geography with aspects of labour economics takes an interest in how, and under which circumstances, redundant workers find new employment in regions (Holm et al 2016;Eriksson et al 2016;Neffke et al 2016;Hane-Weijman et al 2017). These studies could be viewed from a Schumpeterian perspective, where crises such as major closures resulting in the loss of less productive firms are inevitable and even necessary to allow for the growth of more productive firms.…”
Section: Establishment Closure and Creative Destruction In Regional Ementioning
confidence: 99%
“…Schwerdt (2011), however, found in the Austrian context that the age of the workforce decreased gradually over several years and the average earnings of the workforce decreased the year before closure. While the specific effects vary depending on place and industry, it is reasonable to expect that the opportunities for early and late leavers to find new productive uses for their human capital may differ substantially (Eliasson and Storrie 2006;Pfann and Hamermesh 2008;Holm et al 2016). Institutional factors likely play a role in the outcomes, and Sweden's employment protection and welfare system could affect the strategies of firms and workers during the dismantling process (Eliasson and Storrie 2006).…”
Section: Establishment Closure and Creative Destruction In Regional Ementioning
confidence: 99%